Development of a Hydrological Distributed Model Water Resources Assessment in the Mekong River Basin - Kha, Dang Dinh; Ngoc Anh, Tran (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 3DO - 10.25073/2588-1094/vnuees.4591, 2021)
Water resrouces in the Mekong river basin plays a key role for socio-economic development of the downstream region, expecially the Mekong Delta. Therefore, development and validation of SWAT model to provide spatial parameters for better water resources evaluation in Mekong river basin is vital as a result of better consideration the physical characteristics of the study area. In this research, all six hydrological gauges located in mainstream river were utilized for this purpose. The results showed that Nash–Sutcliffe index varied from 0.63 to 0.94 and Pbias varied in range of -14.48%, ÷ +8.67%  confirming the good performance of the model for flow simulation in Mekong river basin and the calibrated spatial parameters reasonably reflect the complex terrain and climate of Mekong river basin.